Legalisasi Ganja untuk Kepentingan Medis: Urgensi Pembaruan Hukum Kesehatan di Indonesia - Karunianingsih, Yemima Putri; Kushantoro, Jonathan; Lowing, Matthew Stanley Edward (LPPM Institut Pendidikan Nusantara Global, 2025)
The legality of cannabis for medical purposes in Indonesia is an evolving issue, driven by increasing scientific evidence of its therapeutic potential and growing public demands for the fulfillment of health rights. This study aims to evaluate the urgency of medical cannabis legalization using a normative juridical approach and an in-depth literature review. The method employed is a literature review with qualitative analysis techniques to identify and examine the gap between the prevailing legal norms in Indonesia and empirical developments and global precedents. The findings indicate that cannabis contains active compounds such as THC and CBD, which have been proven effective in treating various chronic and neurological medical conditions, such as refractory epilepsy, cancer, and cerebral palsy. However, the classification of cannabis as a Category I narcotic under Law No. 35 of 2009 is a major obstacle to its medical use. These findings suggest the need for adaptive legal reform and health policies based on scientific evidence to ensure public access to safe and effective therapeutic options. In addition, the legalization of medical cannabis, accompanied by strict regulation, also has the potential to reduce dependence on opioids and promote the development of the national phytopharmaceutical industry. Therefore, the legalization of medical cannabis should be considered a strategic step in strengthening the healthcare system and protecting human rights in Indonesia.